E-Learning course on gender and inclusion in forest landscape restoration - Elias, Marlene; Gilligan, Molly; Granat, Margaux; Ihalainen, Markus; Monterroso, Iliana; Paez Valencia, Ana Maria (2021)
In this self-paced online course, you will learn the fundamentals of gender and social inclusion in forest landscapes restoration (FLR). The course focuses on gender inequalities, gender-differentiated impacts and opportunities to address inequalities for more equitable and sustainable FLR, to build the abilities and understanding of diverse stakeholders on the gender and FLR nexus.